Implementasi Mitigasi Bencana dalam Kurikulum Pendidikan - Andrias (Jurnal Penelitian Pendidikan Geografi, 2024)
Schools and their educational facilities must be prepared to be safe from disasters and not a place that can endanger the lives of students, teachers and education personnel and other school residents. This research aims to find out the strategic steps in overcoming disaster problems through the education curriculum. This type of research is qualitative research with literature study through reviewing related literature. Then, the analysis of several journals and books related to the discussion material will be described descriptively. The results found that disaster education programs are needed to be able to reduce the risk of natural disasters that may occur at any time. Disaster education is an awareness-building process that starts from building knowledge, understanding and actions that encourage preparedness, prevention and recovery.